Transformasi Mekanisme Pasar Dalam Ekonomi Berbasis Teknologi Digital - Mahera, Rofiqo Meili; Suryadi, Nanda (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The development of digital technology has fundamentally revolutionized the way market mechanisms work. This journal aims to analyze how digital transformation changes the price formation process, interaction patterns between sellers and buyers, and the efficiency of distribution of goods and services. Using a qualitative approach and literature study, it was found that digital technology encourages the creation of a more open, transparent, and responsive market to demand and new challenges such as the dominance of digital platforms and the need for adaptive regulations. The implications of this study are important for policy makers, business actors, and consumers in facing changes in today’s market structure. The transformation of market mechanisms through digital technology brings significant benefits in increasing market efficiency and inclusiveness, but still requires serious attention to aspects of justice, consumer protection, and data governance. This study recommends collaboration between the government, private sector, and society to create a fair, transparent, and sustainable digital market ecosystem.